(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article studies the movement of raw cotton particles on the mesh surface of the cotton separator. The test results of the slider with the recommended content are given.